Present situation and future prospects for Hungarian fruit and vegetable sector - Berecz, Patrícia (Acta Agraria Debreceniensis, 2008)
Changes in people’s lifestyles and the emergence of nutritional science have created favorable opportunities for a boom in fruit and vegetable consumption, which have been fully exploited by the adaptive fruit producer and exporter countries. Unfortunately, Hungary is not one of these countries. Affected by a number of uncertainty factors, the Hungarian fruit and vegetable sector has fallen behind international trends, seeking opportunities for survival (Erdész, 2007).The impacts of the country’s accession to the EU have been more adverse than expected. While no administrative measures are used to control production and the increasing competition and import have put Hungarian producers to a loosing position. The cooperation producers, the well-organized work of professionals and the coordinated activity of producers marketing organizations may resolved some of the problems affecting the sector.The fruit and vegetable sector can also anticipate significant changes during the new seven-years budget period of the CAP reform.With the new drat reform of the sector, the European Commission intends to simplify the common organization of the fruit and vegetable market, improve competitiveness, increase market orientation, promote fruit and vegetable consumption and to continue the environmental efforts.Hungary has had great expectations concerning the reform of market regulation, but the Commission proposal didn’t bear out the expectations, because the new proposal includes insignificant changes in important issues and fails to provide sufficient additional resources for the catching up of he new member states.